Functional analysis of polyphenol oxidase 1 gene in common wheat - Zhai, Shengnan; Liu, Hang; Xia, Xianchun; Li, Haosheng; Cao, Xinyou; He, Zhonghu; Ma, Wujun; Liu, Cheng; Song, Jianmin; Liu, Aifeng; Zhang, Jingjuan; Liu, Jianjun (Frontiers in Plant Science, 2023)
Polyphenol oxidase (PPO) activity is a major cause of the undesirable brown color of wheat-based products. Ppo1, a major gene for PPO activity, was cloned based on sequence homology in previous studies, however, its function and regulation mechanism remain unclear. In this study, the function and genetic regulation of Ppo1 were analyzed using RNA interference (RNAi) and TILLING (Targeting induced local lesions in genomes) technology, and superior mutants were identified. Compared with the control, the level of Ppo1 transcript in RNAi transgenic lines was drastically decreased by 15.5-60.9% during grain development and PPO activity was significantly reduced by 12.9-20.4%, confirming the role of Ppo1 in PPO activity. Thirty-two Ppo1 mutants were identified in the EMS (ethyl methanesulfonate)-mutagenised population, including eight missense mutations, 16 synonymous mutations and eight intron mutations. The expression of Ppo1 was reduced significantly by 6.7-37.1% and 10.1-54.4% in mutants M092141 (G311S) and M091098 (G299R), respectively, in which PPO activity was decreased by 29.7% and 28.8%, respectively, indicating that mutation sites of two mutants have important effects on PPO1 function. Sequence and structure analysis revealed that the two sites were highly conserved among 74 plant species, where the frequency of glycine was 94.6% and 100%, respectively, and adjacent to the entrance of the hydrophobic pocket of the active site. The M092141 and M091098 mutants can be used as important germplasms to develop wheat cultivars with low grain PPO activity. This study provided important insights into the molecular mechanism of Ppo1 and genetic improvement of wheat PPO activity.